Volume 5: 25th International Conference on Design Theory and Methodology; ASME 2013 Power Transmission and Gearing Conference 2013
DOI: 10.1115/detc2013-12700
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Timing in Exploratory Prototyping and Other Activities in Design Projects

Abstract: The importance of prototyping in the design process has been widely recognized, but less research emphasis has been placed on the appropriate timing and detail of so-called “throwaway” prototyping during the preliminary design phase. Based on a study of mid-career professional graduate students, statistically significant correlations were found between the time such prototypes were created and design outcome. Building prototypes early on in the design process, or performing additional rounds of benchmarking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In particular, the simplicity of functional prototypes has been shown to correlate with measures of design outcome [22]. Other work has shown that teams who create prototypes of any type earlier in the design cycle have more successful outcomes [23,24]. Hannah, et al [25] compare the value of prototypes of varying fidelities, from low resolution to high fidelity.…”
Section: Prototyping In Design Processmentioning
confidence: 99%
“…In particular, the simplicity of functional prototypes has been shown to correlate with measures of design outcome [22]. Other work has shown that teams who create prototypes of any type earlier in the design cycle have more successful outcomes [23,24]. Hannah, et al [25] compare the value of prototypes of varying fidelities, from low resolution to high fidelity.…”
Section: Prototyping In Design Processmentioning
confidence: 99%
“…Prototypes enable designers to compare several distinct alternatives as embodied by the aforementioned design language argument in [10], thus exhibiting support for Principle 1. Furthermore, the emphasis on prototyping early and with lo-fidelity [14] enables further concurrent development, thus postponing convergence to a single concept and supporting Principle 2.…”
Section: Deriving the 2 Principles From The 7 Characteristics Of Set-mentioning
confidence: 95%
“…While Ward et al (1995) document Toyota's correlation with frequent prototyping and ostensibly superior design outcomes (i.e. cheaply manufactured, high-quality automobiles), recent work from Häggman et al seeks to explore this relationship in a series of controlled studies [14]. Their research demonstrates statistically significant correlations between prototyping early in the design process and design outcomes.…”
Section: Frequent Prototypingmentioning
confidence: 99%
“…The Pearson correlation rho ranged from 0.02 in year 2014 to -0.55 in year 2013, which means that panel members had different opinions on the success of each product. However, all judges agreed on the top performing and worst performing teams (see [22] for more explanation). Thus we further divided all teams into two categories: the top tier teams and the bottom tier teams, and compared the performance of teams between these two groups.…”
Section: Product Outcome Rankingmentioning
confidence: 96%